2018
DOI: 10.12816/0052815
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Oral Antiviral Treatment for Non-Cardiac HCV Patients

Abstract: Background: The prevalence of hepatitis C virus (HCV) in Egypt is quite high, and the combined oral direct-acting antiviral agents (DAAs) may have impressive results.Objectives: To assess the cardiovascular effects of oral antiviral treatment in non-cardiac HCV patients. Paitents and Methods:The study enrolled 100 patients with positive HCV who were enrolled for the new oral antiviral therapy in the form of Sofosbuvir and dclatsavir with or without ribavirin for 3 or 6 months. All patients on our study were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…The patients who were free of ectopics at baseline did not develop any significant arrhythmia, and there was no change in mean HR and no dynamic ST-T wave change. These results match well earlier studies (20)(21)(22)(23), which concluded that different DAA protocols had no major cardiac events.…”
Section: Discussionsupporting
confidence: 92%
“…The patients who were free of ectopics at baseline did not develop any significant arrhythmia, and there was no change in mean HR and no dynamic ST-T wave change. These results match well earlier studies (20)(21)(22)(23), which concluded that different DAA protocols had no major cardiac events.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding ECG changes, our results didn’t find any statistically significant effect of these drugs on different electrical parameter. This is supported by Allam et al [ 16 ] and Biomy et al [ 17 ] who noticed no statistically significant difference at heart rate, PR interval, QRS duration, QT interval, QTc interval, ST segment and T wave after treatment when compared to their values before treatment. In a recent study conducted in Egypt using 24-h ECG monitoring during treatment, they reported that in non-cardiac patients receiving no cardioactive medications, the combination of sofosbuvir and daclatasvir for the treatment of HCV infection has no effect on heart rate, rhythm, conductivity, or heart rate variability.…”
Section: Discussionsupporting
confidence: 60%
“…12,17 Also, study findings as well as sampling, clinical and echo parameters match well with several studies. [18][19][20] Finally, recent studies have suggested that eradication with DAA regimens is not only safe and tolerable with no major cardiac events, but also significantly reduces cardiovascular adverse events and overall mortality. 21,22 The current study has its limitations.…”
Section: Continued On Next Pagementioning
confidence: 99%